Penerapan Model Pembelajaran Talking Stick dalam Menigkatkan Minat Belajar Peserta Didik dan Hasil Belajar Sejarah Kebudayaan Islam (SKI) Pada Kelas IV di MIN 1 Kendari - siti abu nurhayati (IAIN Kendari, 2020)
This study aims to examine the increase in students' interest and learning outcomes through the application of the Talking Stick learning model in learning Islamic Cultural History (SKI) in class IV at MIN 1 Kendari. This research is classroom action research with Kemmis and Taggar model design. The research procedure includes planning, implementation, observation, evaluation and reflection. This research was conducted at MIN 1 Kendari in class IVB with 35 students as research subjects. Data collection techniques were observation, tests, questionnaires, and documentation which were analyzed descriptively. The results of this study indicate that the application of the Talking Stick learning model can improve learning outcomes of Islamic Cultural History (SKI) and students' interest in learning. The average student learning outcomes in the first cycle was 69.71 with classical completeness 62, 85% then increased in the second cycle with an average of 78.85 with classical completeness 85, 71%. The percentage of students' interest in learning in the first cycle in the medium category was 82,85% and the high category was 17,15% of the 35 students. In cycle II the interest of students in the category increased by 74,28% from 35 students and there was no longer a low category.Keywords: talking sticks, hasil belajar kebudayaan islam (SKI), minat belajar peserta didik